Gemcitabine-Loaded Albumin Nanoparticle Exerts An Antitumor Effect on Gemcitabine-Resistant Pancreatic Cancer Cells Induced by MDR1 and MRP1 Overexpression in Vitro - Kong, Lei; Du, Jiali; Gu, Jichun; Deng, Junyuan; Guo, Yujie; Tao, Baian; Jin, Chen; Fu, Deliang; Li, Ji (Frontiers in Surgery, 2022)
Purpose: Gemcitabine (GEM) is the first-line chemotherapeutic drug for pancreatic cancer treatment in clinical practice. However, many reasons can reduce the efficacy of GEM, among which the high expression of ATP-binding cassette (ABC) transporters is a significant factor. In this study, we aimed to investigate the antitumor effect of gemcitabine-loaded human serum albumin nanoparticle (GEM-HSA-NP) on GEM-resistant pancreatic cancer cells induced by the high expression of ABC transporters, namely multidrug resistance protein 1/P-gp/ABCB1 (MDR1) and multidrug resistance-associated protein 1/ ABCC1 (MRP1). Methods: MDR1 and MRP1 were stably overexpressed via lentiviral transduction in the pancreatic cancer cell lines BxPC3 and PANC1. Proliferation inhibition assays, cell cycle arrest and apoptosis analyses were conducted to examine the antitumor effect of GEM-HSA-NP. In addition, intracellular ATP levels were determined to explore the potential mechanisms implicated preliminarily. Results: When administered to GEM-resistant cancer cells, GEM-HSA-NP displayed its antitumor effect by promoting the inhibition of proliferation, cell cycle arrest, and apoptosis induction. Intracellular ATP depletion, caused by the albumin component of GEM-HSA-NP was proposed to be potentially involved in the modulation of ABC transporter activity. Conclusion: GEM-HSA-NP can effectively overcome GEM-resistance induced by MDR1 and MRP1 overexpression, which highlights its potential value in a clinical setting.